2021
DOI: 10.1097/scs.0000000000007899
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol Granuloma of the Maxillary Sinus Misdiagnosed as Nasal Polyp or Mucocele: Four Cases

Abstract: Cholesterol granuloma is commonly found in the mastoid air cells but is rare in the paranasal sinuses. The most commonly affected sinuses are the frontal sinus, followed by the maxillary sinus. Cholesterol granuloma can be difficult to diagnose because clinical manifestations and radiologic findings are similar to those of other sinonasal disorders. The authors observed 4 cases of cholesterol granuloma that were preoperatively suspected to be nasal polyps or mucoceles. Here, the authors report on their clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 10 publications
1
11
0
Order By: Relevance
“…The occurrence of TB and LEP granulomatous nasal disorders was the least among patients in this study with incidence rate between ∼1-2% only ( Table 1 , Figure 1 A), mostly reported in females of low-socioeconomic background, similar to that of RSC cases. Such a low prevalence of TB and LEP granulomatous nasal disorder have been reported previously in different Asian and Caucasian populations and therefore we have not subsequently focussed on these forms of granulomas ( Foxen, 1979 ; Hassan and Goh, 2012 ; Kim et al., 2021 ; Kulkarni, 2011 ). Lastly, frequent occurrence of RSC, TB and LEP cases in middle-aged females (in comparison with age-matched males) suggest that the responsible pathogen for these cases is likely to be widely present in home or local community spaces in rural areas and lack of social and female hygiene could also play an important role ( Cabral et al., 2022 ; Guarner, 2012 ; Pagan and Ramakrishnan, 2014 ; Ploemacher et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of TB and LEP granulomatous nasal disorders was the least among patients in this study with incidence rate between ∼1-2% only ( Table 1 , Figure 1 A), mostly reported in females of low-socioeconomic background, similar to that of RSC cases. Such a low prevalence of TB and LEP granulomatous nasal disorder have been reported previously in different Asian and Caucasian populations and therefore we have not subsequently focussed on these forms of granulomas ( Foxen, 1979 ; Hassan and Goh, 2012 ; Kim et al., 2021 ; Kulkarni, 2011 ). Lastly, frequent occurrence of RSC, TB and LEP cases in middle-aged females (in comparison with age-matched males) suggest that the responsible pathogen for these cases is likely to be widely present in home or local community spaces in rural areas and lack of social and female hygiene could also play an important role ( Cabral et al., 2022 ; Guarner, 2012 ; Pagan and Ramakrishnan, 2014 ; Ploemacher et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…[3] It is discovered in a wide age range (22-85 years) and most often found in middle-aged males. [3,5,7] Male/female ratio is 3/1. [8] Although, it has no characteristic clinical and radiological symptom, the most frequent hospital admission causes of the patients are single-sided nasal obstruction, nasal discharge and pain.…”
Section: Discussionmentioning
confidence: 99%
“…[8] Although, it has no characteristic clinical and radiological symptom, the most frequent hospital admission causes of the patients are single-sided nasal obstruction, nasal discharge and pain. [3,5,7] However, its most specific symptom is clear golden-yellow nasal discharge. [7] It has been reported to be most commonly seen in frontal sinuses and followed by maxillary sinuses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations